2013
DOI: 10.1007/s10439-013-0855-x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Views of the Biomechanics of Vulnerable Plaque Rupture: A Review

Abstract: This review examines changing perspectives on the biomechanics of vulnerable plaque rupture over the past 25 years from the first FEA showing that the presence of a lipid pool significantly increases the local tissue stress in the atheroma cap to the latest imaging and 3D FEA studies revealing numerous microcalcifications in the cap proper and a new paradigm for cap rupture. The first part of the review summarizes studies describing the role of the fibrous cap thickness, tissue properties and lesion geometry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 85 publications
(202 reference statements)
2
45
0
Order By: Relevance
“…Vengrenyuk et al (2006, 2008), Bluestein et al (2008), Maldonado et al (2012), Cardoso and Weinbaum (2013), and Kelly-Arnold et al (2013) demonstrated that plaque cap with micro-calcification inclusions are associated with elevated stress levels and may be related to plaque rupture. Gao et al (2011) studied carotid plaques and found that critical stress values from symptomatic patients were higher that from asymptomatic patients.…”
Section: Basic Modeling Elements Histology-based Plaque Classificmentioning
confidence: 98%
“…Vengrenyuk et al (2006, 2008), Bluestein et al (2008), Maldonado et al (2012), Cardoso and Weinbaum (2013), and Kelly-Arnold et al (2013) demonstrated that plaque cap with micro-calcification inclusions are associated with elevated stress levels and may be related to plaque rupture. Gao et al (2011) studied carotid plaques and found that critical stress values from symptomatic patients were higher that from asymptomatic patients.…”
Section: Basic Modeling Elements Histology-based Plaque Classificmentioning
confidence: 98%
“…This basic hypothesis was subsequently explored by numerous investigators using 2D and 3D finite element analysis (FEA) and fluid structure interaction numerical models in which various aspects of plaque morphology, tissue properties, residual and fluid shear stress are examined (Cheng et al, 1993; Finet et al, 2004; Tang et al, 2005; Vengrenyuk et al, 2008; Akyildiz et al, 2011; Speelman et al, 2011; Rambhia et al, 2012). These and related studies are described in more detail in a recent review by Cardoso and Weinbaum (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous hemodynamic studies have not investigated the magnitude and distribution of the wall shear stress in severely stenosed aortic arch and its branches. However, the role of high wall shear stresses on the plaque rupture and atherothrombosis has been widely accepted [3,4,12,29]. Accurate knowledge of stresses developed in both healthy and diseased vessels is critical in analyzing biomechanical determinants of plaque rupture [3,29,42].…”
mentioning
confidence: 99%